Influence of Diversity and Inclusion Initiatives on Workplace Innovation in Thailand - Chakrit Yamnam (European Journal of Human Resource, 2024)
Purpose: The aim of the study was to assess the influence of diversity and inclusion initiatives on workplace innovation in Thailand. Materials and Methods: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that organizations that actively promote diversity and inclusion tend to benefit from enhanced creativity and problem-solving capabilities. This is largely because a diverse workforce brings together a wide range of experiences, ideas, and viewpoints, which can lead to more innovative solutions and approaches to challenges. Inclusion ensures that these diverse perspectives are heard and integrated into decision-making processes, creating an environment where employees feel valued and empowered to contribute fully. As a result, companies that prioritize diversity and inclusion often experience higher levels of employee engagement and satisfaction, which further drives innovative thinking and collaborative efforts. Additionally, inclusive practices can help mitigate groupthink, allowing for more robust and resilient strategies. Overall, the integration of diversity and inclusion initiatives within workplace culture is a critical factor in stimulating and sustaining innovation, ultimately leading to better organizational performance and competitiveness. Implications to Theory, Practice and Policy: Social identity theory, resource-based view and innovation diffusion theory may be used to anchor future studies on assessing the influence of diversity and inclusion initiatives on workplace innovation in Thailand. Organizations should tailor diversity training programs to the specific needs of different teams, as the impact of such training can vary based on initial team cohesion and other factors. Policymakers should advocate for the adoption of holistic diversity policies that encompass recruitment, retention, and development practices.